PERFORMANCE OF SEQUENCING ANOXIC/ANAEROBIC MEMBRANE BIOREACTOR (SAM) SYSTEM IN HOSPITAL WASTEWATER TREATMENT AND REUSE - Mohammed Ali I. Al-Hashimia; Talib R. Abbas; Yaser I. Jasema (European Scientific Journal, ESJ, 2013)
In this study, a lab scale SAM system is studied to treat a hospital wastewater to remove organic mattar as well as nitrogen and phosphorus under a different internal recycling time mode. During the operation period, the BOD5 and COD removal efficiency is higher than 98 and 90%, respectively regardless of change of operational conditions. In addition, the results show excellent removal of pathogen and turbidity with average of 98.33 and 99.5%, respectively. The change of Ax/An ratio representing the internal recycling time mode significantly affecting nitrogen and phosphorus removal. As increasing Ax/An ratio nitrogen removal efficiency has increased but phosphorus removal efficiency has decreased. The Ax/An ratio of 2/2, achieving optimal nitrogen and phosphorus removal efficiency of 93% and 83%, respectively. In addition, the SAM system produces high quality effluent which can achieve the Iraqi limits for irrigation purpose for all measured parameters.